Liderança transformacional e inovação social: um estudo em uma instituição financeira - Reis, Antonio Alexandre Mey (2016)
The relationship between companies and the community is highly increasing in competitive economies. Therefore, the projects in social innovation are present to be as valuables instruments in this dialogue. The leaders of the organizations are equally important, whose leadership style can be crucial when facing the continuous transformations that have occurred not only in the company's market, but also in its internal processes. Therefore, the present study is concerned to describe the transformational leadership in the social innovation projects of the financial institution studied. The focused effort here was to explore the degree of the transformational leadership of managers involved in sustainable regional development projects, verifying the aspects that may characterize a good development of social innovation, as well as contextual elements that may either favor or hinder this leadership. As a methodology, a mixed-nature (quantitative and qualitative) research was used based on a case study where the data were obtained through in-depth interviews, and later treated by the content analysis technique. The results obtained from the research reveals that leadership style is an important element in the success of social innovation projects.